Scientific and methodical bases of transformation of agricultural land use - Kolisnyk, H. (Land Management, Cadastre and Land Monitoring, 2017)
Formed scientific and methodical bases of transformation of agricultural land use. Determined essence of the concept of «transformation», «tranformation of agricultural land use», «evaluation of transformation». Thus, in agricultural land use should be understood natural and territorial complex, in which occurs interaction of economic agent with the environment, with the result that forming certain social product (agricultural products), and transformation of agricultural land use – a process of transformation of land use of present social and economic system in a new land use, which is characterized by changing the previous characteristics and properties of land use to a new. At the same time, an important feature of the transformation is withering away of the previous system of economic relations. To determine, if effective occured transformation of agricultural land use, is necessary to conduct environmental and economic evaluation of the transformation of agricultural land use, where ecological and economic evaluation – evaluation of changes of qualitative and quantitative characteristics of agricultural land use as a result of type of social and economic relations and forms of land ownership. In the study suggested structural and logical scheme of transformation of agricultural land use based on formed concepts and statements. Determines the prerequisites of transformation of agricultural land use, based on private ownership of land, so to the main belongs changing of the type of social and economic relations, forms of ownership of land and means of production, the poor state of the environment. As a result of transformation of agricultural land use at market conditions, occured transition from land use of state and collective farms to agricultural formations of market type, зbased on different forms of ownership In the study highlighted the stages of transformation and classification of types of transformation of agricultural land use. Based on the concept of "transformation of agricultural land use" recommended to carry out classification of it’s types: by the result - effective, moderately effective and ineffective; by duration - short, medium and long-term; by the way impact of external and internal factors - evolution, revolutionary; within the meaning of preconditions – economic, social, environmental, political, military and others. Described stages of transformation of agricultural land use, namely: first - imbalance second - unstable and uncertain state; coexistence between forms; third - the establishment of stability and dominance of the new system; fourth - arising of equilibrium state; fifth - post-transformational. The result of of transformation of agricultural land use is the emergence of agricultural formations of market type based on various forms of ownership. In the article analyzes experience of transformation forms of ownership of land in countries such as: Poland, Romania, Slovakia, Czech Republic, where land privatization was carried out by restitution and immediately had the opportunity to freely dispose of land. This had a positive impact on the rapid recovery of agricultural production after the establishment of a market economy. But in Ukraine the land was equally distributed among rural population, much of which has never conducted an independent business that has affected the efficiency of agricultural production. After transformation of land relations in our state occurred redistribution of lands between the categories of landowners and land users. The main land users were newly established agricultural enterprises, farms, private farms and citizens for agricultural commodity production. The specific of transformation was the concentration of agricultural land in large agricultural enterprises, which are the main producers of agricultural products and services and in fact - legal successors of collective farms and state farms with employees. Study development of agricultural land use in Ukraine shows that, rent of lands was one of the main ways to implement the landowners of their rights to land. On the basis of rental relations formed majority of agricultural land use of market type. Keywords: land use, transformation processes, transformation, valuation, restructuring, land reform.